2012
DOI: 10.2147/jpr.s31800
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of duloxetine adherence and persistence in patients with fibromyalgia

Abstract: ObjectivesAdherence to medication for the treatment of fibromyalgia (FM) is predictive of lower overall health-care costs, and thus a lower burden on both patients and providers. The objectives of this study were to examine the predictors of adherence to and persistence with duloxetine therapy among commercially insured FM patients, and to identify subgroups of patients with high duloxetine persistence and adherence.Study designThis cross-sectional, retrospective study analyzed medical and pharmacy records ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
6
1
3
Order By: Relevance
“…These rates are higher compared with those previously reported for IBD, excluding patients on anti-TNF therapies who had similarly high rates of adherence (2527). Although data on medication adherence in FGID patients are sparse, our observed adherence exceeds the 29–45% reported for patients with non-GI functional disorders, such as fibromyalgia (28,29). We hypothesized that adherence would be low in the subgroup of FGID patients on TCAs given their stigmatization as “psychiatric medications” (6,7).…”
Section: Discussioncontrasting
confidence: 71%
“…These rates are higher compared with those previously reported for IBD, excluding patients on anti-TNF therapies who had similarly high rates of adherence (2527). Although data on medication adherence in FGID patients are sparse, our observed adherence exceeds the 29–45% reported for patients with non-GI functional disorders, such as fibromyalgia (28,29). We hypothesized that adherence would be low in the subgroup of FGID patients on TCAs given their stigmatization as “psychiatric medications” (6,7).…”
Section: Discussioncontrasting
confidence: 71%
“…Pharmacological treatment includes pain moderators such as selective serotonin reuptake inhibitor antidepressants (alone) and so-called dual (serotonin and noradrenaline), non-selective tricyclic agents (such as amitriptyline and cyclobenzaprine) and anticonvulsant agents (such as pregabalin and gabapentin) 3,18 . Adherence to FM pharmacological treatment is considered low worldwide, and varies among the different drugs, with tricyclic agents being the most rapidly abandoned, and adherence was higher in the group that received more selective antidepressants [18][19][20]22 . Among the more selective, noradrenaline and serotonin reuptake inhibitors, also known as dual inhibitors, similar to tricyclics, produce central analgesia acting on descending inhibitory nerve pathways.…”
Section: Impact On the Quality Of Life Of Patients With Fibromyalgiamentioning
confidence: 99%
“…Di Matteo et al 4 concluded that the risk of non-adherence is 27% higher in this group, regardless the underlying disease to be treated. Cui et al 20 evaluated the adherence of patients with fibromyalgia to the treatment with duloxetine and showed that one-third of them had a strong adherence, and among them, the predictive factors for better adherence were age above 35 years and previous use of selective antidepressants (serotonergic inhibitors or serotonergic and noradrenergic). The same group of investigators, in a study involving more than 18,000 patients, concluded that adherence and persistent use of duloxetine were similar in groups of patients with depressive disorder, FM and osteoarthritis, and significantly higher than the results found for patients with chronic lower back pain 21 .…”
Section: Impact On the Quality Of Life Of Patients With Fibromyalgiamentioning
confidence: 99%
“…High adherence was indicated as MPR ≥ 0.8. Patients with high adherence and persistence with duloxetine were significantly older and had prior antidepressant use [3].…”
Section: Gateway To Fibromyalgiamentioning
confidence: 99%